Influence of planting designs on winter thermal comfort in an urban park - Karimi Afshar, Nima; Karimian, Zahra; Doostan, Reza; Habibi Nokhandan, Majid (Journal of Environmental Engineering and Landscape Management, 2018)
Various planting designs behave in different ways on microclimate and thermal comfort due to mainly distinct features of vegetation type and ratio. The papers simulated the microclimate behavior and thermal comfort of different planting design scenarios of an urban park using ENVI-met model. We measured temperature, relative humidity and wind velocity during the coldest period of 2016. Seven scenarios of planting design with different types and ratios of vegetation were simulated. In scenario of evergreen trees, humidity was relatively high while temperature and wind velocity were decreased. Simulated grass covered park and deciduous trees showed higher temperature and wind velocity. Scenario of grasses and the scenarios with high ratio of deciduous trees in comparison with other scenarios indicated lower wind speeds. The findings can be seen as a possibility of improvement of winter thermal comfort, considering a proper planting design as an important step in order to achieve Citizen Satisfaction.